‘Cannibalism’ of exogenous DNA sequences: The ancestral form of adaptive immunity which entails recognition of danger - Devaux, Christian A.; Pontarotti, Pierre; Nehari, Sephora; Raoult, Didier (Frontiers in Immunology, 2022)
Adaptive immunity is a sophisticated form of immune response capable of retaining the molecular memory of a very great diversity of target antigens (epitopes) as non-self. It is capable of reactivating itself upon a second encounter with an immunoglobulin or T-cell receptor antigen-binding site (paratope) with a known epitope that had previously primed the host immune system. It has long been considered that adaptive immunity is a highly evolved form of non-self recognition that appeared quite late in speciation and complemented a more generalist response called innate immunity. Innate immunity offers a relatively non-specific defense (although mediated by sensors that could specifically recognize virus or bacteria compounds) and which does not retain a memory of the aggressors. But this notion of recent acquisition of adaptive immunity is challenged by the fact that specific recognition mechanisms already existed in prokaryotes that may be able to specifically auto-protect against external aggressors. This recognition mechanism can be considered a primitive form of specific (adaptive) non-self recognition. It is based on the fact that many archaea and bacteria use a genome editing system that confers the ability to appropriate viral DNA sequences allowing prokaryotes to combat aggressors through a mechanism very similar to adaptive immunity. This is called 'viral DNA predation', or 'DNA cannibalism'. For several years evidence has been accumulating, highlighting the crucial role of 'DNA cannibalism' in the fundamental processes related to adaptive immunity and leading to a change in the dogma that adaptive immunity appeared late in speciation.